THE MATTER ON THE INVESTIGATION OF CASES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article examines the issue of cases’ investigation in linguistics. It analyzes the opinions expressed about the issue of cases in world languages, that the former and main functions of cases are not reflected in their logical meanings, but in the denotation and relationships of time. The scientific views on grammatical cases in German and Karakalpak languages are described in the article.